Carbon footprint of maize produced in Argentina - Bongiovanni, Rodolfo; Tuninetti, Leticia; Vigneau, Pedro; Gayo, Sofía (Ediciones INTA, 2025)
The carbon footprint (CFP) of a product, such as maize, is defined by the ISO standards as the sum of greenhouse gas (GHG) emissions and GHG removals in a production system, expressed as carbon dioxide equivalent (CO2eq) and based on a life cycle assessment using the single impact category of climate change. It is the measure of one of the impacts caused by human activities on the environment. The general objective of this study was to calculate the CFP of maize produced in Argentina by quantifying the significant GHG emissions and removals during the life cycle of the crop from the extraction of materials for the production of inputs to the delivery of the harvested grain at the farm gate. The declared unit is 1 kg of maize at the farm gate. The data were obtained through the “Survey of Applied Agricultural Technology” and were provided by the Buenos Aires Grain Exchange through an agreement to use the data for this purpose. The data included two sowing dates (early and late) and three technological levels (high, intermediate and low) in each of the 16 maize-producing agroeconomic zones. The data corresponded to the 2021-2022 crop season, when 51,336,000 tons were produced in an area of 7,440,000 hectares. The results show that the national average carbon footprint is 1,248 kg CO2eq per harvested hectare and 0.178 kg of CO2eq per kg of maize at the farm gate. A sensitivity analysis considering GHG removal from no-tillage showed that the CFP values decreased by 12% (1,099 kg CO2eq/ha and 0.157 kg CO2eq/kg). In addition, when the use of no-tillage and cover crops was considered, an additional CFP decrease of 2 kg CO2eq/ha was estimated, resulting in 1,097 kg CO2eq/ha and 0.156 kg CO2eq/kg. The CFP was 3% lower in late maize than in early maize; however, when the removals were considered, this relationship was reversed, with the CFP being 1% lower for early maize. When considering the transportation and handling of grain from the field to the port, including loading onto a ship under FOB condition, the emissions increased by 15% compared to the baseline situation, reaching 0.204 kg of CO2eq per kg. This work is useful for all the actors in the maize value chain because (a) it provides a comprehensive environmental scenario of primary production, showing the environmental hotspots; (b) it facilitates the communication of environmental information to society; (c) it shows possible reductions of emissions and costs; and (d) it allows for comparisons between countries or production systems.